Effect of ω-9MUFAs in Fat Emulsion on Serum Interleukin-6 in Rats with Lipopolysaccharide-induced Lung Injury - Qianqian, Zheng; Gui, Mei; Min, Yang; Qingfeng, Zhang; Xiufen, Xu; Zejun, Fang; Yahong, Li; Mingwei, Ye (Combinatorial Chemistry & High Throughput Screening, 2024)
Aim: This study aimed to investigate how ω-9 MUFAs in fat emulsion affect serum IL- 6 levels in rats with lipopolysaccharide (LPS)-induced lung injury. Background: Research suggests that acute lung injury (ALI) develops acute respiratory distress syndrome (ARDS) due to the activation of many inflammatory factors. ALI may be treated by reducing inflammation. Fat emulsion is used in parenteral nutrition for critically ill patients to regulate the body's inflammatory response. It is mostly made up of ω-9 MUFAs (Clinoleic), which can regulate the inflammatory response. Objective: The effect of ω-9MUFAs on the secretion of IL-6 in ALI rats was studied in order to provide a basis for the rational use of fat emulsion in clinical practice and provide new ideas for the diagnosis and treatment of ALI. Methods: The control, model, and -9MUFAs groups consisted of 18 female Sprageue-Dawley (SD) young rats (180 ± 20 g). The SD young rats received normal saline and were not operated. LPS-induced ALI animals received tail vein injections of normal saline. SD young rats were first triggered with acute lung injury by LPS (3 mg/kg) and then injected with 3 mg/kg of ω-9MUFAs via the tail vein. The expression levels of IL-6, an activator of signal transduction transcription 3 (STAT3), transforming growth factor-β (TGF-β), and glycoprotein 130 (GP130) in serum and lung tissues were determined by ELISA and Western blot methods. Results: Compared with the model group, the survival rate of rats in the ω-9 MUFAs group was significantly increased, and the difference was statistically significant (p<0.05). Compared with the model group, the lung pathology of rats in the ω-9 MUFAs group was significantly improved, and the expression levels of IL-6, TGF-β1, GP130, IL-1 and other proteins were significantly decreased. The difference was statistically significant (p<0.05). Conclusion: In LPS-induced lung injury, ω-9MUFAs may alleviate symptoms by inhibiting the IL-6/GP130/STAT3 pathway.
Keywords: LPS